Morphological and Molecular Identification of Anagrus 'atomus' Group (Hymenoptera: Mymaridae) Individuals from Different Geographic Areas and Plant Hosts in Europe. Issue 1 (28th April 2016) - Zanolli, P.; Martini, M.; Mazzon, L.; Pavan, F.
Abstract: Morphological identification and molecular study on the COI gene were simultaneously conducted on Anagrus Haliday ' atomus ' group individuals collected in the field in Italy or supplied from a UK biofactory. Females were morphologically identified as A. atomus L. and A. parvus Soyka sensu Viggiani (= A. ustulatus sensu Chiappini). Alignment of COI gene sequences from this study permitted recognition of a total of 34 haplotypes. Phylogenetic and network analyses of molecular data not only confirmed that A. atomus is a species distinct from A. parvus, but also suggested that two species may be included within morphologically identified A. parvus. Different geographical distribution and frequency of haplotypes were also evidenced. For males considered in this study, morphometric analyses revealed a character that could be useful to discriminate A. atomus from A. parvus . Both species were found in vineyards and surrounding vegetation, confirming the potential role of spontaneous vegetation as a source of parasitoids for leafhopper control in vineyards.